Public Policy Implementation in Health Service Delivery in Nepal: A Heuristic Study - Paudel, Narendra Raj (Innovative Research Journal, 2022)
Heuristically, implementation puts a stronghold in its research areas. The three generations of implementation provide a glimpse of how the hardcore of heuristic policy implementation is elaborated; how auxiliary hypotheses were set and how these were tested. Still, there is room for further research. On this purview, the reproductive health policy implementation research in Nepal is still limited heuristically. Therefore, the causal relationship of health policy implementations was analysed based on the negative and positive heuristic methods of Lakatos. The finding revealed that there is a strong causal relationship among these factors like the developed countries. In the case of Nepal, the hardcore hypothesis is not changed even if the output health policy implementation is found weak. At the same time, auxiliary policies were intervened to concretize the hardcore policy.